Efficacy of Pasteurised Donor Human Milk on the Growth of Preterm Neonates: A Research Protocol of a Randomised Control Trial - Akansha Sisodia; RJ Meshram; Sagar Karotkar (Journal of Clinical and Diagnostic Research)
Introduction: Growth restriction is a common complication affecting a significant proportion of Very Low Birth Weight (VLBW) infants, with estimates suggesting that up to 97% of these vulnerable newborns are impacted. While Maternal Own Milk (MOM) is the gold standard for nutrition, pasteurised Donor Human Milk (DHM) offers a safe and nutritious alternative when MOM is not available. This research investigation aims to examine and compare the effects of MOM and DHM on growth parameters and outcomes in preterm infants. Need of the Study: Preterm infants are disproportionately vulnerable to neurodevelopmental delays and other complications, underscoring the importance of identifying effective interventions to support their growth and development. While MOM is widely recognised as the optimal source of nutrition, the potential benefits of DHM warrant further investigation. Given the limited research directly comparing MOM and DHM, this study aims to address this knowledge gap and explore the impact of these nutritional sources on the developmental outcomes of preterm neonates. Aim: To compare the efficacy of pasteurised DHM on anthropometric indices (Weight/Head circumference/Length) of preterm neonates until the age of discharge. Materials and Methods: This randomised controlled trial will be conducted in the Neonatal Intensive Care Unit (NICU) and Ward of Jawaharlal Nehru Medical College and AVBRH Hospital, Sawangi, Wardha, Maharashtra, India, from January 2024 to January 2026. All preterm infants born before 37 weeks of gestation and receiving enteral nutrition during the study duration will be enrolled. Participants will be randomly assigned to one of three groups based on the type of milk consumed: MOM, DHM, or a combination of both. Anthropometric measurements {Weight (once every day in the morning from 6 AM to 8 AM), head circumference and length (both once weekly on every Sunday in the morning from 6 AM to 8 AM)} will be recorded regularly until discharge. Recording anthropometric measurements regularly (daily/weekly) at consistent times (6 AM-8 AM) enables timely detection of growth issues, prompt intervention and informed discharge planning. This approach ensures accuracy, consistency and comprehensive tracking of patient growth and development until discharge. Data analysis will be performed using Statistical Package for the Social Sciences (SPSS) version 21.0 software. Analysis of Covariance (ANCOVA) will be employed to compare anthropometric indices among groups. Weight Gain Velocity (WGV) will be calculated by dividing the weight on the 10th day by the weight on the 1st day, multiplying by 1,000 and expressing the result in grams per kilogram per day (g/kg/day). Logistic regression analysis will be used to compare the incidence of Feeding Intolerance (FI) among groups.